2017
DOI: 10.18203/2320-1770.ijrcog20174039
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal outcome in severe preeclampsia and eclampsia: a retrospective study in a tertiary care centre

Abstract: Background: Hypertensive disorders of pregnancy are a leading cause of maternal and perinatal mortality and morbidity worldwide. In India, they account for the third most important cause of maternal mortality. The objectives of this study were to evaluate maternal and perinatal outcome and complications in cases with severe preeclampsia and eclampsia. Methods: A retrospective study was carried out on 110 women with severe preeclampsia and eclampsia in a tertiary care referral centre over a period of 15 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 13 publications
(15 reference statements)
3
18
0
Order By: Relevance
“…The findings of our study are consistent with the findings of the study done by Pillai SS et alwho ndings are similardocumented 42.72% patients in the age group of 26-30 years. 4 These findings are related to the fact that most women conceive first time in this age group. 2 Two third of the subjects (69.11%) were primigravidas and approximately one third of them (30.89%) were multigravidas.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The findings of our study are consistent with the findings of the study done by Pillai SS et alwho ndings are similardocumented 42.72% patients in the age group of 26-30 years. 4 These findings are related to the fact that most women conceive first time in this age group. 2 Two third of the subjects (69.11%) were primigravidas and approximately one third of them (30.89%) were multigravidas.…”
Section: Discussionmentioning
confidence: 94%
“…3 Maternal mortality worldwide is systematically reviewed by World Health Organisation (WHO) and it was reported that 16% of maternal deaths were due to hypertensive disorders in developed countries. 4 According to WHO report 2008, eclampsia constitutes for 12% of all maternal deaths in developing countries. 5 In Asia and Africa, hypertensive disorders constituted for 9% of maternal mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Table 1) Similar findings were seen by Pillai et al in where 19% had deranged LFT, 15% had deranged KFT and 7% had hemolysis on peripheral smear. 9 Authors found that 92% of cases presented at gestational age of >32 weeks (Figure 3).…”
Section: Discussionmentioning
confidence: 99%